Identification of Fraud Components and Political Factors Influencing Fraud in Financial Statements - Bandanipour, Maryam; Nakhaei, Habibollah; Hajiha, Zohreh; Nakhaei, Karim (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: The purpose of this research was to identify the components of fraud and the political factors affecting fraud in financial statements. Methodology: The research method was fundamental in objective, qualitative in data type, and Delphi in data collection method. The population consisted of 20 experts from academia and finance, economic experts related to auditing and fraud, senior managers of leading companies listed on the Tehran Stock Exchange, and economic managers and professors. The research tool included targeted non-random interviews. For data analysis, the Delphi method was utilized. Findings: The findings revealed that the components of fraud and political factors influencing fraud in financial statements include the fraud triangle and diamond (pressure, opportunity, rationalization, and capability) and political factors (individual and organizational). Conclusion: In conclusion, this study highlights the intricate interplay between individual and organizational political factors and the traditional elements of fraud, providing insights into the mechanisms through which political dynamics influence fraudulent practices in financial reporting. This understanding could guide the development of more effective detection and prevention strategies.